2021
DOI: 10.1021/acs.est.1c01189
|View full text |Cite
|
Sign up to set email alerts
|

H2-Based Membrane Catalyst-Film Reactor (H2-MCfR) Loaded with Palladium for Removing Oxidized Contaminants in Water

Abstract: Scalable applications of precious-metal catalysts for water treatment face obstacles in H2-transfer efficiency and catalyst stability during continuous operation. Here, we introduce a H2-based membrane catalyst-film reactor (H2-MCfR), which enables in situ reduction and immobilization of a film of heterogeneous Pd0 catalysts that are stably anchored on the exterior of a nonporous H2-transfer membrane under ambient conditions. In situ immobilization had >95% yield of Pd0 in controllable forms, from isolated sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 85 publications
4
29
0
Order By: Relevance
“…This peaking at 1.2 g Pd 0 /m 2 occurred because the defluorination of PFOA with H 2 occurred mainly at the water–Pd 0 interface. We hypothesize that while increasing the loading of nanoparticles increased the total active surface area, excessive Pd 0 coverage resulted in aggregation of Pd 0 NPs, which decreased the accessible specific surface area and led to lower catalytic activity . In addition, a thick and agglomerated Pd film may have hindered H 2 transfer to Pd 0 sites near the bulk liquid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This peaking at 1.2 g Pd 0 /m 2 occurred because the defluorination of PFOA with H 2 occurred mainly at the water–Pd 0 interface. We hypothesize that while increasing the loading of nanoparticles increased the total active surface area, excessive Pd 0 coverage resulted in aggregation of Pd 0 NPs, which decreased the accessible specific surface area and led to lower catalytic activity . In addition, a thick and agglomerated Pd film may have hindered H 2 transfer to Pd 0 sites near the bulk liquid.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that while increasing the loading of nanoparticles increased the total active surface area, 28 excessive Pd 0 coverage resulted in aggregation of Pd 0 NPs, which decreased the accessible specific surface area and led to lower catalytic activity. 14 In addition, a thick and agglomerated Pd film may have hindered H 2 transfer to Pd 0 sites near the bulk liquid. Because 1.2 g Pd 0 /m 2 gave the best removal and defluorination performance, it was chosen as the optimal addition in this study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive agglomeration of PdNPs would not only block the contact between catalytic active sites and SMX but also induce greater mass transfer resistance between H 2 and PdNPs, thus lowering the SMX removal rate. 40 It has also been reported that an excessive Pd loading (over 0.44 g/m 2 ) could lead to the decrease of nitrite reduction by 22% in a similar MPfR system. 40 According to these observations, we can conclude that the Pd dosage has a crucial impact on the SMX removal efficiency and should be controlled at a proper level (e.g., 100 mg/dm 2 under the experimental condition) for long-term SMX removal.…”
Section: Effects Of Operatingmentioning
confidence: 93%
“…According to the surface topography of the membrane at different magnifications (Figure S3), obviously nanosize Pd adhered to the membrane, verifying the successful construction of PdNPs film to the membranes, which is similar to that reported by Zhou et al (2017, 2021). 40,41 XPS was further used to analyze the valency of precipitates attached to the surface of membranes (Figure 1B), and it was found that Pd(0) was dominant, indicating Pd(II) was reduced to Pd(0), which was well-deposited to the membranes.…”
Section: Methodsmentioning
confidence: 99%